U-Shaped Relationship of Low-Density Lipoprotein Cholesterol With Risk of Severe COVID-19 From a Multicenter Pooled Analysis - Gong, Jiao; Chen, Yaqiong; Jie, Yusheng; Tan, Mingkai; Jiang, Zhaofang; Yuan, Lianxiong; Cao, Jing; Li, Ganwen; Chong, Yutian; Qu, Jiuxin; Shi, Yaling; Hu, Bo (Frontiers in Cardiovascular Medicine, 2021)
Low-density lipoprotein cholesterol (LDL-C) is a well-known risk factor for coronary heart disease but protect against infection and sepsis. We aimed to disclose the exact association between LDL-C and severe 2019 novel coronavirus disease (COVID-19). Baseline data were retrospectively collected for 601 non-severe COVID-19 patients from two centers in Guangzhou and one center in Shenzhen, and patients on admission were medically observed for at least 15 days to determine the final outcome, including non-severe (n=460) and severe group (severe and critical cases) (n=141). Among 601 cases, 76 (12.65%) received lipid-lowering therapy; the proportion of patients taking lipid-lowering drugs in severe group was higher than non-severe group (22.7% vs 9.6%). We found a U-shaped association between LDL-C level and risk of severe COVID-19 using restricted cubic splines. Using univariate logistic regression analysis, odds ratios for severe COVID-19 for patients with LDL-C less than or equal to 1.6 mmol/L (61.9 mg/dL) and above 3.4 mmol/L (131.4 mg/dL) were 2.29 (95% confidence interval 1.12–4.68; p =0.023 ) and 2.02 (1.04–3.94; p =0.039), respectively, compared to those with LDL-C of 2.81–3.40 mmol/L (108–131mg/dL); following multifactorial adjustment, odds ratios were 2.61 (1.07–6.37; p=0.035) and 2.36 (1.09–5.14; p=0.030). Similar results yielded using 0.3 mmol/L and 0.5 mmol/L categories of LDL-C and sensitivity analyses. Both low and high LDL-C levels were significantly associated with higher risk of severe COVID-19. Although our findings do not necessarily imply causality, they suggest that clinicians should pay more attention to lipid-lowering therapy in COVID-19 patients to improve clinical prognosis.